Advancing understanding of HRM in small and medium-sized enterprises (SMEs): critical questions and future prospects. Issue 16 (6th September 2022) - Harney, Brian; Gilman, Mark; Mayson, Susan; Raby, Simon
Abstract: A notable paradox of HRM research is that while small and medium-sized enterprises (SMEs) form the dominant private sector employer across the globe, they remain dramatically underrepresented in scholarship. This is significant as there are a number of SME specific characteristics that shape HRM in this context, raising questions around the relevance and applicability of dominant understanding of HRM. In this paper we outline six such SME characteristics captured by the acronym RECIPE and outline their implications for HRM. We then introduce seven special issue papers which serve to advance understanding of HRM in SMEs. Drawing together key insights, we conclude by proposing a number of routes for future research and deeper contextualisation of HRM in SMEs. These include broadening the theoretical palette, challenging conventional assumptions, moving beyond an exclusive HPWS focus, incorporating employee perspectives, coupled with the need to cast a wider methodological net.